Machine Learning - Analyzing Olympic Sports Combining Sensors and Vision AI - Ashley, K. (MSDN Magazine, 2018)
It`s an area of urgency for the U.S. Olympic Team. There are four diving events—3-meter springboard, 10-meter platform, 3-meter synchronized diving and 10-meter synchronized diving—that account for 24 total available medals in each Olympics. Sensors and ML promise to improve training regimes and maximize athlete performance on the biggest stage.